A Narrative Review of Human Reliability Analysis (HRA) Techniques in Various Industries in Iran - Ehsanollah Habibi; Seyed Mahdi Mousavi; Mahsa Jahadi Naeini (International Journal of Environmental Health Engineering)
Human error is a significant factor contributing to occupational accidents across various industries. To address this issue, Human Reliability Analysis (HRA) techniques have emerged as valuable tools for evaluating and mitigating the risks associated with human error. These methods allow for a thorough assessment of how and why errors occur, the likelihood of these errors leading to accidents, and the potential consequences of such incidents. This research comprehensively examines several HRA techniques, detailing their applications in a wide array of sectors, including railway, healthcare, petrochemical, and engineering. By analyzing literature sourced from reputable databases such as the Web of Science, Scopus, Islamic World Science Citation, and Scientific Information Database core collection from 2009 to 2023, this review highlights key findings and trends in HRA studies. Interestingly, the investigation of HRA in Iran has been relatively limited, with most studies concentrated on the health and petrochemical industries. Recognizing the potential for improvement, this review advocates for the broader implementation of HRA methods across all sectors to enhance safety protocols and minimize the likelihood of human errors leading to accidents.